Monetary theory - Tew, Brian (Beverly Hills, Calif.: Sage Publications, 1969)
The purpose of this book is to provide a common basis for the better understanding of two kinds of literature on monetary economics: on the one hand the works of academic theorists and on the other the commentaries of the City journalist and the banks reviews.
Bibliography: p. 60-61.
usc 20/09/18
Loans
Keywords: Money; Great Britain